Gut microbiota regulate Alzheimer's disease pathologies and cognitive disorders via PUFA-associated neuroinflammation. Issue 11 (11th January 2022) - Chen, Chun; Liao, Jianming; Xia, Yiyuan; Liu, Xia; Jones, Rheinallt; Haran, John; McCormick, Beth; Sampson, Timothy Robert; Alam, Ashfaqul; Ye, Keqiang
Abstract : Objective: This study is to investigate the role of gut dysbiosis in triggering inflammation in the brain and its contribution to Alzheimer's disease (AD) pathogenesis. Design: We analysed the gut microbiota composition of 3×Tg mice in an age-dependent manner. We generated germ-free 3×Tg mice and recolonisation of germ-free 3×Tg mice with fecal samples from both patients with AD and age-matched healthy donors. Results: Microbial 16S rRNA sequencing revealed Bacteroides enrichment. We found a prominent reduction of cerebral amyloid-β plaques and neurofibrillary tangles pathology in germ-free 3×Tg mice as compared with specific-pathogen-free mice. And hippocampal RNAseq showed that inflammatory pathway and insulin/IGF-1 signalling in 3×Tg mice brain are aberrantly altered in the absence of gut microbiota. Poly-unsaturated fatty acid metabolites identified by metabolomic analysis, and their oxidative enzymes were selectively elevated, corresponding with microglia activation and inflammation. AD patients' gut microbiome exacerbated AD pathologies in 3×Tg mice, associated with C/EBPβ/asparagine endopeptidase pathway activation and cognitive dysfunctions compared with healthy donors' microbiota transplants. Conclusions: These findings support that a complex gut microbiome is required for behavioural defects, microglia activation and AD pathologies, the gut microbiome contributes to pathologies in an AD mouse model and that dysbiosis of the human microbiome might be a risk factor for AD.